IMPROVED LAPAROSCOPIC VERSUS OPEN HERNIOPLASTY FOR POSTOPERATIVE VENTRAL HERNIAS: THE INDEPENDENT EFFECT OF THE REPAIR METHOD ON OUTCOMES (International Conference on Education, Psychology and Humanities, 2026)
Modern mesh-based repair has substantially reduced recurrence of postoperative ventral hernias, yet wound complications, pain and prolonged disability after open surgery remain a problem. Objective evidence on the independent effect of the repair method on early and long-term outcomes is needed to justify the wider use of improved laparoscopic techniques.